Zonificación hídrica y calidad del agua en la zona receptora de la microcuenca Elvira, cantón Quilanga - Ortega Abad, Luis Alfredo (2016)
In the present investigation has determined those areas with potential for water recharge in the microwatershed Elvira, Quilanga, for which arose as main objective: to update the status information situational water resource in the high part of the micro-watershed Elvira -Quilanga, in the perspective of propose its territorial restructuring (zoning) for the maintenance of the quality and quantity of water for the purposes of human consumption. To address the present study was first conducted a biophysical characterization, socio-economic, political, institutional and legal, of the receiving area of the micro-watershed, was later analysis of quality of water including two times (rainy and dry), was finally raised a zoning proposal in the areas of water recharge through geographic information systems, taking into account criteria mostly water. The information generated evidence that today the receiving area, have problems of loss of vegetative cover product of activities such as agriculture and livestock that is in progressive increase within the slopes, and with it the increase of water polluting agents that can be show in the analysis of water quality made, both for rainy season and for the dry season. With regard to the supply and demand of water, the average flow exists to meet the basic needs of human consumption as established in the World Health Organization (WHO), 50 l /day/ inhabitant. Finally, within the internal water zoning is presented that the zone with the highest priority is given to the aspect of the Tone and externally to the slope the salt shaker.